Seroprevalence Of HIV Among Truck Drivers - Singh G. B; Dhaliwal D. S; Sekhon A. S; Kaur K; Singh S; Kaur P (Wolters Kluwer Medknow Publications, 1999)
Research questions: What is the prevalence of HIV among truck drivers? Objective: To study the seroprevalence of HIV among truck drivers. Study design: Cross-sectional. Setting: Truck Union of Patiala City and National Highway No. 1. Participants: One thousand truck drivers working along the National Highways. Study variables: Age, educational status, marital status, and sexual behaviour. Statistical analysis: Proportions. Results: One thousand truck drivers from 14 states of India and Nepal were interviewed and tested for HIV. Forty-three (4.3%) truck drivers were detected positive for HIV, All the HIV positive truck drivers were below 45 years of age. Lower educational status was associated with higher HIV seropositivity. More of the married truck drivers were HIV positive than the unmarried. HIV seropositivity was also been associated with relatively shorter and more frequent out station visits. Sex with commercial sex workers and irregular use of condom were associated with a higher HIV seropositivity.